Stigmatizing Attitudes Toward Patients With Psychiatric Disorders Among Medical Students and Professionals - Oliveira, Ana Margarida; Machado, Daniel; Fonseca, João B.; Palha, Filipa; Silva Moreira, Pedro; Sousa, Nuno; Cerqueira, João J.; Morgado, Pedro (Frontiers in Psychiatry, 2020)
Abstract Introduction: Stigma attached to mental health encompasses discrimination and exclusion of psychiatric patients and hinders their opportunities to have more productive and fulfilling lives. Moreover, stigma also exist among health professionals and therefore it hampers the provision of treatment and care and the promotion of mental well-being. This manuscript intends to assess and compare the levels of stigmatization towards patients with mental illness between medical students and doctors from different specialties. Methods: The Portuguese version of Attribution Questionnaire (AQ27) was used to assess the attitudes of medical students (n=203), non-psychiatry doctors (n=121) and psychiatry specialists (n=29) from University of Minho and 3 hospitals in the region of Braga, Portugal (Hospital de Braga, Hospital Senhora da Oliveira and Hospital de Fafe). Results: Psychiatrists were the group that displayed lower levels of stigmatizing attitudes in all the items of the AQ27, followed by the students. The regression analyses revealed that professional group and presence of a relative with mental illness were the factors that have a significant impact on the levels of stigmatization. Conclusions: Mental illness stigma is widely spread in community and reaches not only general population but also health professionals. Psychiatrists presented lower levels of stigma compared with non-psychiatry physicians and medical students. We found that stigma is related with age and the presence of relatives with psychiatric disorders. These findings highlight the critical relevance of raising awareness on this topic and therefore break stereotypes to reduce the negative consequences of stigma.